2017
DOI: 10.1155/2017/1271670
|View full text |Cite
|
Sign up to set email alerts
|

Intramyocardial Injection of Recombinant Adeno‐Associated Viral Vector Coexpressing PR39/Adrenomedullin Enhances Angiogenesis and Reduces Apoptosis in a Rat Myocardial Infarction Model

Abstract: Cotransfer of angiogenic and antiapoptotic genes could be the basis of new gene therapy strategies for myocardial infarction. In this study, rAAV-PR39-ADM, coexpressing antimicrobial peptide (PR39) and adrenomedullin (ADM), was designed with the mediation of recombinant adeno-associated virus. In vitro, CRL-1730 cells were divided into four groups, namely, the sham group, the AAV-null group, the NS (normal saline) group, and the PR39-ADM group. Immunocytochemistry analysis, CCK-8 assays, Matrigel assays, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…Moreover, hTRX could inhibit thrombosis by reducing tissue factor activity and further prevent the injury of the ischemic tissue (31). Consistent with An et al report, intramyocardial injection of recombinant adeno-associated viral vector coexpressing pr39/adrenomedullin enhances angiogenesis and reduces apoptosis in a rat myocardial infarction model (32). Our study showed that the gene fusion system rAAV/hTRX-PR39 can effectively ameliorate acute cerebral infarction-induced ischemic injury by promoting angiogenesis and inhibiting cell apoptosis.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, hTRX could inhibit thrombosis by reducing tissue factor activity and further prevent the injury of the ischemic tissue (31). Consistent with An et al report, intramyocardial injection of recombinant adeno-associated viral vector coexpressing pr39/adrenomedullin enhances angiogenesis and reduces apoptosis in a rat myocardial infarction model (32). Our study showed that the gene fusion system rAAV/hTRX-PR39 can effectively ameliorate acute cerebral infarction-induced ischemic injury by promoting angiogenesis and inhibiting cell apoptosis.…”
Section: Discussionsupporting
confidence: 89%
“…HUVECs are accepted and widely used in vitro investigations for endothelial disorders of arteries [61] , [62] , [63] , [64] . Although HUVECs exhibit phenotypic and functional differences versus human arterial endothelial cells (HAECs) [65] , considering the limited lifespan and the unstable characteristics of the primary HAECs [66] , we adopted the immortalized HUVEC cell line [64] in our study that are generally better characterized and more stable in their endothelial traits [66] .…”
Section: Discussionmentioning
confidence: 99%
“…The plasma level of ADM is higher in patients with diabetes compared with healthy individuals, and further increased in patients with diabetic complications [23]. Additionally, ADM involves in dilation of the coronary, inhibition of vascular remodeling and reduction of fibroblast proliferation and extracellular matrix synthesis, which may further contribute to reduction of infarct size, ischemia-reperfusion injury, and ischemia-induced arrhythmias [34]. Mid-regional pro-adrenomedullin (MR-proADM), a surrogate marker for adrenomedullin, has been reported to be a risk factor for the loss of renal function in patients with T2DM and be a predictor of in-hospital mortality in patients with acute MI complicated by cardiogenic shock [35,36].…”
Section: Discussionmentioning
confidence: 99%